The Relationship Of Waist Flexibility Towards Smash Skills In Volley Ball Extracurricular Athletes In Sma N 13 Bengkulu Utara - Aas Sugiarto; Supriyanto Supriyanto; Mesterjon Mesterjon (Penerbit Jurnal Indonesia, 2021)
This study aims to determine whether there is a relationship between waist flexibility and smash skills in volleyball extracurricular athletes at SMA N 13 Bengkulu Utara. This type of research is correlational research with the research method used is pure experimental method. The population of this study were all volleyball athletes at SMA N 13 North Bengkulu as many as 15 people. The sampling technique in this study is total sampling. Total sampling is a sampling technique where the total population is less than 100 so that the entire population is used as the research sample, namely: 15 people. The variables of this study were waist flexibility tests and smash skills of volleyball athletes at SMA N 13 Bengkulu Utara. The data collection technique used the Waist Flexibility test and the smash test. The data analysis technique used was the normality and homogeneity test. Based on the results of the research above, it can be concluded that the waist flexibility test is related to the smash of volleyball athletes at SMA N 13 Bengkulu Utara. The results of the data p-value (Sig) = 0.000 < = 0.05 means that there is a significant relationship between waist flexibility and smash skills. 13 North Bengkulu.”, accepted.